(untitled) (KONFERENSIYA, 2025)
This article explores the linguo-pragmatic features of translating international economic correspondence and identifies key factors influencing the adequacy and equivalence of translation in the economic domain. Economic correspondence, as a specialized form of written business communication, requires a high degree of terminological precision, pragmatic awareness, and intercultural competence. The study highlights typical translation challenges related to lexical non-equivalence, pragmatic misinterpretation, genre specificity, and structural complexity of economic texts. Special emphasis is placed on the translator’s background knowledge, communicative intent analysis, and the ability to interpret legal, financial, and commercial terminology accurately. The findings demonstrate that economic translation is inherently interdisciplinary and demands strong linguistic, cognitive, and analytical skills to ensure accurate intercultural communication